2022
DOI: 10.1097/nrl.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Thrombosis With Topical Estrogen-Progesterone Use in a Young Heterosexual Male

Abstract: Introduction: Our report sheds light on the risk of topical hormonal use in relation to cerebral venous sinus thrombosis. We diagnosed our patient with cerebral venous thrombosis (CVT) using computed tomography venogram, then detailed history and examination were obtained, and thorough blood tests and imaging were done to exclude other causes of CVT like thrombophilias, infections, and malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A 2023 case report by Aldraihem et al. showed extensive cerebral venous thrombosis in the right internal jugular vein, sigmoid, transverse, and straight cerebral venous and the application of crushed OCPs mixed with water topically on the scalp was found to be the most important predisposing factor 9 . In a meta‐analysis by Amoozegar et al., it was found that women taking OCPs had 7.59 times higher risk of developing CVST as compared to those not 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A 2023 case report by Aldraihem et al. showed extensive cerebral venous thrombosis in the right internal jugular vein, sigmoid, transverse, and straight cerebral venous and the application of crushed OCPs mixed with water topically on the scalp was found to be the most important predisposing factor 9 . In a meta‐analysis by Amoozegar et al., it was found that women taking OCPs had 7.59 times higher risk of developing CVST as compared to those not 10 .…”
Section: Discussionmentioning
confidence: 99%